Pengaruh Modal Usaha dan Pendidikan terhadap Keberhasilan Usaha di KTT Manik Pertiwi Desa Wanagiri - Ni Gusti Putu Ayu Pertami Yanti; Kadek Rai Suwena (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
The purpose of this analysis is to realize the effect of business capital and education on business success at the Manik Pertiwi Summit, Wanagiri Village. The analysis is a causal analysis. The population of this analysis is the farmers in the Manik Pertiwi Summit with a total sample of 57 people. The methods used for data collection are questionnaires and documentation. The data analysis technique used for the analysis is multiple linear regression with t test and F test in order to realize the influence of the independent variable on the dependent variable partially and simultaneously. The results of the study confirm that (1) there is an effect of venture capital on business success. This is indicated by the value of tcount = 3.121 with a significance level of 0.003 <0.05 (2) there is an effect of education on business success. This is indicated by the value of tcount = 3.540 with a significance level of 0.001 < 0.05 (3) there is an effect of business capital and education on business success. The analysis is stated by the value of Fcount = 8.333 with a significance level of 0.001 <0.05.